Faktor Perilaku Seksual pada Remaja - Rini Rahmadani; Akbar Asfar; Ramli, Rahmawati (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2023)
Sexual behavior is any behavior that can be triggered by sexual desire carried out between two people of the opposite sex or the same sex. This study aims to determine what factors are associated with sexual behavior in adolescents at SMK BAZNAS SUL-SEL. The research design used a quantitative approach with a cross-sectional method. The determination of the sample was carried out using a proportional stratified random sampling technique with a sample size of 91 people. The bivariate test used in this study was the chi square test. The results showed that the environment was not related to sexual behavior with a p value = 0.596, while family was associated with sexual behavior with a p value = 0.001, peers associated with sexual behavior with a p value = 0.006, and social media was associated with sexual behavior with a p value. = 0.035. It can be concluded that there is no significant relationship between environmental factors and sexual behavior, and there is a significant relationship between family, peer and social media factors with sexual behavior in adolescents at SMK BAZNAS SUL-SEL. The suggestion from the researcher is that it is hoped that the results of this study can be used as a reference for researchers and can be useful for respondents in understanding factors related to sexual behavior in adolescents.